2016
DOI: 10.1111/jcpe.12588
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled clinical study evaluating effectiveness and safety of a volume‐stable collagen matrix compared to autogenous connective tissue grafts for soft tissue augmentation at implant sites

Abstract: Aim To test whether or not the use of a collagen matrix (VCMX) results in short‐term soft tissue volume increase at implant sites non‐inferior to an autogenous subepithelial connective tissue graft (SCTG), and to evaluate safety and tissue integration of VCMX and SCTG. Methods In 20 patients with a volume deficiency at single‐tooth implant sites, soft tissue volume augmentation was performed randomly allocating VCMX or SCTG. Soft tissue thickness, patient‐reported outcome measures (PROMs), and safety were asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
283
2
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 141 publications
(314 citation statements)
references
References 38 publications
19
283
2
1
Order By: Relevance
“…During further healing, remodeling processes of soft tissue transplants and soft tissue substitutes are common and were described in previous preclinical and clinical experiments [16,20,27,28]. Moreover, it has also been observed that the tissues underlying the soft tissue grafts undergo remodeling processes as well [18].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…During further healing, remodeling processes of soft tissue transplants and soft tissue substitutes are common and were described in previous preclinical and clinical experiments [16,20,27,28]. Moreover, it has also been observed that the tissues underlying the soft tissue grafts undergo remodeling processes as well [18].…”
Section: Discussionmentioning
confidence: 92%
“…In vitro and preclinical data showed favorable histological and volumetric results in terms of tissue integration and volume gain [17][18][19]. Although recent clinical data show similar volume gain when 4 augmenting implant sites with SCTG or VCMX [20], long term data monitoring volume changes at implant sites are still scarce .…”
Section: Introductionmentioning
confidence: 99%
“…51,52 VCMX is made of collagen and * Geistlich Pharma, Wolhusen, Switzerland. This graft has also been called volume-stable collagen matrix (VCMX) since one of its main advantages is the ability to maintain a good volume stability.…”
Section: Volume-stable Collagen Matrixmentioning
confidence: 99%
“…This graft has also been called volume-stable collagen matrix (VCMX) since one of its main advantages is the ability to maintain a good volume stability. 51,52,54 In contrast to CM that has been used also in an open environment, VCMX requires a submerged healing. undergoes a cross-linking providing volume stability and some elasticity at the same time.…”
Section: Volume-stable Collagen Matrixmentioning
confidence: 99%
“…6365 These collagen matrices are treated like gingival or subepithelial connective tissue but are a nonautogenous tissue substitute. Although they have some preliminarily favorable results, the success is limited to small and simple defects.…”
Section: Soft Tissue Regenerationmentioning
confidence: 99%